PENGARUH KOMPETENSI, KOMITMEN DAN KOMPENSASI TERHADAP KEPUASAN KERJA DAN DAMPAKNYA TERHADAP KINERJA PEGAWAI DINAS PEMUDA DAN OLAHRAGA ACEH - Ahmadun Syawal; Nasir Azis; Faisal Faisal (FEB - Unsyiah, 2018)
Many factors affect the performance of an employee, such as job satisfaction, competence, commitment and compensation. The purpose of this research is to know 1) The state of competence, commitment, compensation, job satisfaction and performance of employee of Dinas Pemuda dan Olahraga Aceh. 2) The influence of competence on job satisfaction of employee of Dinas Pemuda dan Olahraga Aceh 3) The influence of commitment to job satisfaction of Dinas Pemuda dan Olahraga Aceh. 4) The effect of compensation on the job satisfaction of the employees of Dinas Pemuda dan Olahraga Aceh. 5) The influence of competence on the performance of Dinas Pemuda dan Olahraga Aceh. 6) Influence of commitment to performance of employee of Dinas Pemuda dan Olahraga Aceh. 7) The effect of compensation on the performance of the employees of Dinas Pemuda dan Olahraga Aceh. 8) The influence of job satisfaction on the performance of employees of Dinas Pemuda dan Olahraga Aceh. 9) The influence of competence on the performance through job satisfaction of Dinas Pemuda dan Olahraga Aceh. 10) The influence of commitment to performance through job satisfaction of employee of Dinas Pemuda dan Olahraga Aceh. 11) The effect of compensation on performance through job satisfaction of the employees of Dinas Pemuda dan Olahraga Aceh. The number of respondents in this study was 126 people. Data were analyzed by using structural equation model (SEM) which operated with AMOS software (analysis moment structure). The results showed that the competence, commitment, compensation, job satisfaction and performance of the employee is good. Competence and compensation significantly affect employee job satisfaction. Competence, commitment and compensation have a significant effect on employee performance. Satisfaction has a significant effect on the performance. Competence and commitment have a significant effect on performance through job satisfaction. Commitment has no significant effect on performance through job satisfaction